The impact of financial crisis on coronary artery disease burden in Greece - Elias A. Sanidas; Theodoros G. Papaioannou; Dimitrios P. Papadopoulos; Konstantina Tatsi; Maria Velliou; Nikolaos Dalianis; Ioannis Paizis; George Anastasiadis; Glaukos Kelepesis; Maria Bonou; Kontantinos Tsioufis; John Barbetseas (Hellenic Journal of Cardiology, 2019)
Background: Economic crisis poses an immense threat to public health worldwide and has been linked to cardiovascular morbidity and mortality. Greece is facing a distinctive recession over the recent years. However, the exact impact on coronary artery disease (CAD) burden has not been adequately addressed. Methods: Demographic, clinical, and angiographic data of 3895 hospitalized patients were retrospectively studied. Patients were classified into two groups: those before crisis (2006–2007, n = 1228) and those during crisis (2011–2015, n = 2667). Results: All data before and during crisis were compared. During crisis, patients presented with less acute coronary syndrome (ACS – 45.5% vs. 39.9%, p < 0.001). Subsequently, there were more patients without CAD (23.7% vs. 35.1%, p < 0.001) or one-vessel disease (20.5% vs. 23%, p < 0.001). The prevalence of traditional risk factors decreased significantly or remained stable except obesity (26.3% vs. 31.4%, p = 0.002). A significant increase in the examined females (23.6% vs. 26.7%, p = 0.04) was also observed. Conclusions: The burden of CAD in Greece was partially affected during the financial crisis. Even though the incidence of ACS was decreased, more women and more patients with no- or single-vessel disease were referred for cardiac catheterization. In addition, the prevalence of traditional risk factors for CAD did not increase except obesity confirming the “obesity paradox.” It seems that the impact of traditional risk factors for CAD is not an immediate process and is somewhat related to living conditions or other exogenous and social factors. Keywords: Financial crisis, Risk factors, Coronary artery disease